2022
DOI: 10.3389/fphar.2022.818179
|View full text |Cite
|
Sign up to set email alerts
|

Active Components of Traditional Chinese Medicinal Material for Multiple Myeloma: Current Evidence and Future Directions

Abstract: Multiple myeloma (MM) is a hematological malignancy characterized by clonal expansion of plasma cells in bone marrow, leading to the overproduction of monoclonal immunoglobulins. The clinical manifestations resulting from monoclonal proteins and malignant cells include signs of end-organ damage, such as hypercalcemia, renal failure, anemia, and bone lesions. Despite improvement in the survival of MM patients with use of myeloma-targeted and immunomodulatory therapies, MM remains an incurable disease. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Activates apoptosis through inducing oxidative stress. 82,30,78 © 2023 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License Sinomenine Selectively induces apoptosis in primary MM cells and MM cell lines due to inhibiting the IL-6-induced activation of STAT3.…”
Section: Down-regulation Of Iqgap1mentioning
confidence: 99%
“…Activates apoptosis through inducing oxidative stress. 82,30,78 © 2023 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License Sinomenine Selectively induces apoptosis in primary MM cells and MM cell lines due to inhibiting the IL-6-induced activation of STAT3.…”
Section: Down-regulation Of Iqgap1mentioning
confidence: 99%
“…The results indicated that total flavonoids have a role in regulating T cell apoptosis and related genes in corticosterone rats ( Liu et al, 2020 ). The active components found in Chinese herbs induce apoptosis by regulating apoptotic protein families such as the Bcl-2 family and the Caspase family, as well as impacting apoptosis signaling pathways like the p53 pathway and the NF-κB pathway ( Yu et al, 2022 ).…”
Section: Mechanisms Of Chinese Herbs Against Infectious Diseasesmentioning
confidence: 99%
“…Baicalein is a coumarin-like derivative extracted from Chinese herbs that induces early osteoblast differentiation through activation of the MAP kinase/NF-κB signaling pathway, and this activation is associated with increased expression of osteoblast differentiation markers. In addition, baicalin induced the differentiation of MC3T3-E1 in mouse osteoblasts [ 71 , 72 , 73 , 74 , 75 ]. Resveratrol (RSV) is a natural compound present in various plant species that reduces the growth of myeloma cell lines (RPMI 8226 and OPM-2) in a dose-dependent manner and inhibits ligand-receptor activator (RANKL)-induced osteoclast differentiation.…”
Section: Multiple Myeloma (Mm) and Osteosarcomamentioning
confidence: 99%